The Sublethal Effects of a Systemic Insecticide on the Vine Mealybug Parasitoids Anagyrus sp. near pseudococci (Girault) and Coccidoxenoides perminutus (Timberlake) (Hymenoptera: Encyrtidae) - Mgocheki, N.; Addison, P. (South African Journal of Enology and Viticulture, 2016)
Imidacloprid is a systemic insecticide used for the control of the vine mealybug Planococcus ficus. However, biological control of P. ficus is the primary alternate management method recommended for the integrated control of this pest. We therefore aimed to establish the detrimental effects on the development of Anagyrus. sp. near pseudococci and Coccidoxenoides perminutus feeding on imidacloprid-contaminated vine mealybugs as indicated by the subsequent emergence and survival of the F1 generation. The results imply that A. sp. near pseudococci and C. perminutus were equally susceptible to imidacloprid, based on probit analysis. However, survival was significantly different between the control and insecticide treatment for C. perminutus (χ2 = 23.80; d.f. = 3; p < 0.001), but not for A. sp. near pseudococci (χ2 = 5.07; d.f. = 3; p = 0.17). As this study was laboratory based, the effect of imidacloprid on populations of parasitoids in the field should be assessed further. Treatment recommendations to minimise the impact on parasitoids are discussed briefly.